DIFFUSIVE FRACTIONATION OF U-SERIES RADIONUCLIDES DURING MANTLE MELTING AND SHALLOW-LEVEL MELT-CUMULATE INTERACTION - Van Orman J.A.; Saal A.E.; Bourdon B.; Hauri E.H. (My University, 2006)
U-series radioactive disequilibria in basaltic lavas have been used to infer many important aspects of melt generation and extraction processes in Earth’s mantle and crust, including the porosity of the melting zone, the solid mantle upwelling rate, and the melt transport rate. Most of these inferences have been based on simplified theoretical treatments of the fractionation process, which assume equilibrium partitioning of U-series nuclides among minerals and melt. We have developed a numerical model in which solid-state diffusion controls the exchange of U-series nuclides among multiple minerals and melt. First the initial steady-state distribution of nuclides among the phases, which represents a balance between diffusive fluxes and radioactive production and decay, is calculated. Next, partial melting begins, or a foreign melt is introduced into the system, and nuclides are again redistributed among the phases via diffusion. U-series nuclides can be separated during this stage due to differences in their diffusivity; radium in particular, and possibly protactinium as well, can be strongly fractionated from slower-diffusing thorium and uranium. We show that two distinct processes are not required for the generation of 226Ra and 230Th excesses in mid-ocean ridge basalts, as has been argued previously; instead the observed negative correlations of the (226Ra/230Th) activity ratio with (230Th/238U) and with the extent of trace element enrichment may result from diffusive fractionation of Ra from Th during partial melting of the mantle. Alternatively, the (226Ra/230Th) disequilibrium in mid-ocean ridge basalts may result from diffusive fractionation during shallow-level interaction of mantle melts with gabbroic cumulates, and we show that the results of the interaction have a weak dependence on the age of the cumulate if both plagioclase and clinopyroxene are present.
Keywords: CLINOPYROXENE; DIFFUSION; FRACTIONATION; MANTLE STRUCTURE; MID-OCEAN RIDGE; PARTIAL MELTING; PLAGIOCLASE; RADIONUCLIDE